Scribal memory and word selection: text criticism of the Hebrew Bible - Person, Raymond F. (Text-critical studies, 2023)
"What were ancient scribes doing when they copied a manuscript of a literary work? This question is especially problematic when we realize that ancient scribes preserved different versions of the same literary texts. In Scribal Memory and Word Selection: Text Criticism of the Hebrew Bible, Raymond F. Person Jr. draws from studies of how words are selected in everyday conversation to illustrate that the same word-selection mechanisms were at work in scribal memory. Using examples from manuscripts of the Hebrew Bible, Person provides new ways of understanding the cognitive-linguistic mechanisms at work during the composition/transmission of texts. Person reveals that, while our modern perspective may consider textual variants to be different literary texts, from the perspective of the ancient scribes and their audiences, these variants could still be understood as the same literary text"--Page 4 of cover